2019
DOI: 10.1101/808840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A stable leading strand polymerase/clamp loader complex is required for normal and perturbed eukaryotic DNA replication

Abstract: The eukaryotic replisome must faithfully replicate DNA and cope with replication fork blocks and stalling, while simultaneously promoting sister chromatid cohesion. Ctf18-RFC is an alternative PCNA loader that links all these processes together by an unknown mechanism. Here, we use integrative structural biology combined with yeast genetics and biochemistry to highlight the specific functions that Ctf18-RFC plays within the leading strand machinery via an interaction with the catalytic domain of DNA Pol ε. We … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 78 publications
(117 reference statements)
1
3
0
Order By: Relevance
“…A recent genome-wide analysis of PCNA occupation on the leading and lagging strands consistently showed that Ctf18-RLC preferentially loads PCNA on the leading strand, and that the RFC complex preferentially loads PCNA on the lagging strand 28 . This study, along with other studies, showed that interaction with Pol ε contributes to the recruitment of Ctf18-RLC to replication forks 28,29 . However, Ctf18 is not essential for bulk DNA replication and cannot substitute for Rfc1 deletion.…”
Section: Pcna Loadingsupporting
confidence: 82%
See 3 more Smart Citations
“…A recent genome-wide analysis of PCNA occupation on the leading and lagging strands consistently showed that Ctf18-RLC preferentially loads PCNA on the leading strand, and that the RFC complex preferentially loads PCNA on the lagging strand 28 . This study, along with other studies, showed that interaction with Pol ε contributes to the recruitment of Ctf18-RLC to replication forks 28,29 . However, Ctf18 is not essential for bulk DNA replication and cannot substitute for Rfc1 deletion.…”
Section: Pcna Loadingsupporting
confidence: 82%
“…Ctf18 mutants defective with Pol ε-binding were originally reported to be sensitive to hydroxyurea and defective in the replication checkpoint, as shown by reduced Rad53 phosphorylation 63 . On the other hand, two recent reports show that hydroxyurea sensitivity and reduced Rad53 phosphorylation are not observed in either Pol ε-binding-defective dcc1 mutants or Dcc1-binding-defective Pol ε mutants 28,29 . However, the same paper showed that Rad52 foci, markers for recombination, and Psf1 phosphorylation, a marker for late origin firing, both of which are normally suppressed by checkpoint activation, are increased in Pol ε-bindingdefective ctf18 mutants treated with hydroxyurea.…”
Section: Checkpoint Activationmentioning
confidence: 87%
See 2 more Smart Citations